Pengaruh Biaya Produksi dan Harga Jual Padi Terhadap Pendapatan Petani di Desa Margodadi - Lestari, Deva; Carmidah, Carmidah (PROGRAM STUDI AKUNTANSI SYARIAH FAKULTAS SYARIAH DAN EKONOMI ISLAM IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2024)
The selling price of rice is highly dependent on market conditions and seasons. During the main harvest, the price of rice tends to fall due to abundant supply, while at certain times the price can soar due to limited availability. In addition, high production costs are also a problem. The increase in the price of agricultural inputs such as fertilizers, medicines, and labor costs, increases the burden of production that must be borne by farmers. The purpose of this study was to measure the effect of production costs and selling prices of rice on farmers' income. Data collection through questionnaires and documentation. The sample used in this study was 85 respondents, with the community in farmers in Margodadi Village, Tumijajar District, West Tulang Bawang Regency. The data analysis techniques used were instrument testing, multiple linear analysis, and hypothesis testing. The results of this study indicate that production costs do not have a significant effect on the level of farmer income in Margodadi Village, selling prices have a significant effect on farmer income in Margodadi Village and production costs and selling prices simultaneously affect farmer income in Margodadi Village.